Nekateri individualni in socialni napovedniki bralnih dosežkov slovenskih dijakov v raziskavi PISA 2009 - Podlesek, Anja (Šolsko polje, 2011)
The paper presents the predictive model of reading achievement of Slovene upper secondary-school students in PISA 2009. It includes selected predictors at an individual level and predictors of family and learning environment. From the original database, first-year students from four types of upper-secondary school programs (n = 4250) were selected into our sample. We used two-level linear models to analyse the relation between the predictors and reading achievement. Individual and social predictors explained about 8% of the total variance in reading achievement. When the type of the upper-secondary school program was additionally entered into the model, the predictors explained 60% of the total variance. Higher reading achievements were found in girls, students with higher socio-economic status, and in those who speak Slovene at home, have higher interest in reading, perceive higher teacher's stimulation of students' reading engagement, and use metacognitive strategies in reading, interpret literary texts and read online more frequently.
Keywords: vzgoja in izobraževanje; education; PISA 2009; high-school students; dijaki; reading literacy; bralna pismenost; bralnost; psychosocial factors; predictors; branje; multilevel linear models; psihosocialni dejavniki; Slovenia; Slovenija; raziskave